Rendimiento Laboral en los Funcionarios del Gobierno Autónomo Descentralizado Parroquial de la Isla de Bejucal - Mayorga Mora, Yomira Eloisa (2018)
The public administration in the institutions is of the utmost importance, it is linked to the State, which is in charge of organizing the available resources and budgets that it distributes to different entities of the country and to guarantee the socioeconomic development of all, this means that the administration reaches several places and proportionally covers the needs of citizens. The administrative management in the global institutional environment has a fundamental or key aspect, for the execution and productivity of the tasks carried out in the institutions, to fulfill the planned objectives, to contribute to the development and growth of the same. Therefore, the management seeks to use scarce resources to the maximum and achieve their long-term goals, through four basic functions of the administration: planning, organizing, directing and controlling.